Mixed-phenotype Acute Leukemia with Trilineage Differentiation in a 3-year-old Child - I Gusti Ayu Mardewi; Anak Agung Wiradewi Lestari; I Nyoman Wande; Ni Nyoman Mahartini (Journal of Applied Hematology)
Mixed-phenotype acute leukemia (MPAL) is characterized by the expression of markers from multiple hematopoietic lineages, including myeloid, B-cell, and T-cell origins. This case report describes a 3-year, 8-month-old girl who presented with swelling in both eyes, initially accompanied by lumps on the neck and a fever that subsided with antipyretics. After the neck lumps resolved, eye swelling began in the right eye and later progressed to the left eye. Bone marrow aspiration confirmed the presence of mixed-lineage leukemia, revealing myeloblasts with Auer rod, monoblast, and lymphoblast. Leukemia phenotyping identified a mixed lineage involving myeloid, B-cell, and T-cell markers, supporting the diagnosis of MPAL. The patient was treated according to the acute lymphoblastic leukemia induction therapy protocol with vincristine and daunorubicin, and fluid hydration and allopurinol were taken to prevent tumor lysis syndrome. This case highlights the diagnostic complexity and need for a comprehensive treatment approach in managing MPAL.